Isolation of Steroidal Saponin from Dracaena umbratical / Raudhatul Jannah Mohd Zuki et al. - Mohd Zuki, Raudhatul Jannah; Mahmud, Zurina; Yusoff, Zaini; Lajis, Nordin (Universiti Teknologi MARA, Perlis, 2012)
Steroidal saponins are important class of components found in plants that play several crucial bioactivities based on previous studies. One known steroidal saponin was successfully isolated from Dracaena umbratica, a shrub of Dracaenaceae family. Dracaena umbratica also known as ‘Senjuang’ among local people. The isolation of a white amorphous steroidal saponin was conducted via normal phase vacuum liquid chromatography eluted with methanol. Its structure was established by spectroscopic analysis as 3-O-[α-L-rhamnopyranosyl (14)-α-L-rhamnopyranosyl (14)-β-D-glucopyranosyl]-25(R)-spirost-5-en-3β-ol.